Determining the dependence of potassium glyceroxide catalytic activity on storage conditions - Morozova, Liubov; Glavatchuk, Vita; Minieiev, Oleksandr; Tkachenko, Tetiana; Marushko, Larysa; Korolchuk, Svitlana; Savchuk, Tanya; Kolesnyk, Anastasiia; Mohutova, Valentyna; Mylostyvyi, Roman (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the catalytic activity of potassium glyceroxide in the chemical transesterification reaction of palm olein. Transesterification is an important method for obtaining fats with desired properties, surfactants, alternative biofuels, etc. Industrial catalysts for chemical transesterification are explosive, flammable, and quickly lose activity. Alkali metal glyceroxides are safer and more stable catalysts. The dependence of potassium glyceroxide catalytic activity (CAS Number 43110-90-3) on storage conditions was examined. The criterion for the catalyst's effectiveness was an increase in palm olein melting point by more than 12 °C after transesterification. Refined, bleached, and deodorized palm olein (DSTU 4438:2005, CAS Number 93334-39-5) was used, with the following parameters: peroxide value 0.18 ½ O mmol/kg, acid value 0.12 mg KOH/g, melting point 22.2 °C. The conditions under which potassium glyceroxide retains its effectiveness were determined: storage time of 8 weeks at a temperature of 20 °C; storage time of 15 weeks at 5 °C. The melting point difference between original and transesterified olein was 12.5 °C and 13.6 °C, respectively. The chromatographic analysis confirmed changes in the triglyceride composition of the transesterified olein. It was found that the industrial catalyst sodium methoxide, stored under these conditions, lost its effectiveness. The melting point difference between original and transesterified olein was 7.5 °C and 9.7 °C, respectively. The obtained data allow for efficient transesterification of fats using potassium glyceroxide as a more stable catalyst, which can be pre-produced and stored at the enterprise